(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This case study presents some factors involved in modulating the behaviors of a drug using adolescent. Therefore, the adolescent’s and a family member’s levels of self-efficacy and hope were assessed, whereas both received a brief intervention for adolescent drug use with parent sessions. The adolescent’s drug use and motivation were also investigated. The main results indicate that the adolescent showed less motivation at follow-up concerning actions, although his ambivalence and his awareness regarding drug use problems increased. The adolescent lapsed back to tobacco use, albeit presented a structured routine at 14 months after the posttest. Based on the results, when considering the importance to improve positive aspects in adolescence, in order to do so, their caretakers should also be supported.